Green Logistics Development in Vietnam: An Assessment of Impact Factors and Recommendations from an Enterprise Perspective - Dung, Vu Dinh; Ngoc, Nguyen Thi Viet (Journal of Cultural Analysis and Social Change, 2025)
Under the growing pressure of environmental protection, green logistics is an unavoidable trend of development within the context of globalization and the commitment of enterprises towards sustainable development. In Vietnam, green logistics has been increasingly adopted by enterprises and, although there has been some positive initial progress, it still exposes numerous shortcomings, particularly in the case of small and medium enterprises that still face numerous challenges. With a literature review and preliminary surveys in several enterprises in Hanoi, the study has identified five key groups of factors that affect the extent of green logistics adoption from an enterprise perspective: (1) Managers’ awareness of the environment; (2) Financial capacity; (3) Logistics infrastructure and technology; (4) Government’s supportive policies; and (5) Capability of digital technology adoption. Among them, the prominent obstacles include high initial investment, inadequate infrastructure, and poor-oriented policies. However, some enterprises have started their positive transition by using clean vehicles and digitizing their supply chains that shows both potential and internal motivation for green transformation in logistics industry. From findings of the study, the article gives a number of recommendations to promote the development of green logistics in Vietnam, including completion of a legal framework, increase of financial support, investment in infrastructure, and enhancement of technological capability for enterprises. The group of authors expects to provide a practical foundation for policymaking as well as to orient Vietnamese small and medium enterprises in specific actions in their transition toward environmentally friendly logistics models.